Multiscale fibril structure of hollow windmill palm fibers. Issue 21 (November 2021) - Chen, Changjie; Wang, Zhong; Zhou, Sui; Wang, Guohe; Bao, Limin; Wang, Xinhou
Windmill palm fiber is a kind of multicellular lignocellulose fiber material. Multiscale structure is an essential factor in mechanical properties and applications. The multiscale fibrils under sulfuric acid treatment had been prepared to improve the understanding of the macro-, micro-, and nanoscale structure of the windmill palm fiber. Scanning electron microscopy, atomic force microscopy, wide-angle X-ray scattering, and X-ray diffraction were used to analyze these samples' structure. Furthermore, the result showed that the elementary fibril diameter was 4–10 nm, whereas that of the microfibrils was 20–70 nm. The diameters of macrofibril and macrofibril bundles were 0.4–1.0 µm and 1.2–5.5 µm, respectively. The elementary fibril assembled into spiral microfibril with an angle of 46°. The crystallinity of nanofibril extracted from windmill palm fiber was about 62%.